2019
DOI: 10.1111/os.12508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cross‐Linked Hyaluronate Scaffold on Cartilage Repair: An In Vivo Study

Abstract: Objective To determine the safety and effectiveness of a cross‐linked sodium hyaluronate (CHA) scaffold in cartilage repair. Methods Physicochemical properties of the scaffold were determined. The safety and effectiveness of the scaffold for cartilage repair were evaluated in a minipig model of a full‐thickness cartilage defect with microfracture surgery. Postoperative observation and hematological examination were used to evaluate the safety of the CHA scaffold implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The CECs will either be press‐fitted into the cartilage defects without any additional fixation or fixation will be performed using a thin layer of fibrin glue. The CECs will either be press‐fitted into the cartilage defects without any additional fixation 57,58 or fixation will be performed using a thin layer of fibrin glue 59,60 . Additionally, it is possible to improve the quality of a cartilaginous CEC using culturing in a bioreactor and low‐oxygen conditions for a more precise reproduction of stimuli that ensure cell viability in a body 61–63 …”
Section: Resultsmentioning
confidence: 99%
“…The CECs will either be press‐fitted into the cartilage defects without any additional fixation or fixation will be performed using a thin layer of fibrin glue. The CECs will either be press‐fitted into the cartilage defects without any additional fixation 57,58 or fixation will be performed using a thin layer of fibrin glue 59,60 . Additionally, it is possible to improve the quality of a cartilaginous CEC using culturing in a bioreactor and low‐oxygen conditions for a more precise reproduction of stimuli that ensure cell viability in a body 61–63 …”
Section: Resultsmentioning
confidence: 99%
“…Most of those studies have been conducted as clinical trials [ 16 , 22 ], giving us the objective measures such as histology and clinical scores, which naturally is of greatest interest. Numerous animal studies have been conducted as well, prior to the use of these scaffolds in humans [ 12 , 32 ], providing us with the histology of the repaired tissue when using different scaffolds or without them [ 12 , 32 ]. However, the studies on the basic level, preceding both animal models and clinical trials are not abundant and the authors of this article have failed to find them in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 HA is a glycosaminoglycan and essential component of the ECM synthesized by chondrocytes, fibroblasts, and type B synovial cells and discharged into the synovial fluid. 7,14,27 HA is an essential substrate for chondrocyte growth, metabolism, and maintenance of the chondrocyte phenotype and promotes ECM formation. 27 Yoshioka et al showed that the crosslinked HA hydrogel, Gel-One Ò , remained at the intra-articular injection site in a rat model for 91 days after administration, 28 demonstrating its effectiveness as a depot style drug delivery vehicle.…”
Section: Introductionmentioning
confidence: 99%